2011
DOI: 10.1002/prot.23130
|View full text |Cite
|
Sign up to set email alerts
|

Antibody modeling assessment

Abstract: A blinded study to assess the state of the art in three-dimensional structure modeling of the variable region (Fv) of antibodies was conducted. Nine unpublished high-resolution x-ray Fab crystal structures covering a wide range of antigen-binding site conformations were used as benchmark to compare Fv models generated by four structure prediction methodologies. The methodologies included two homology modeling strategies independently developed by CCG (Chemical Computer Group) and Accerlys Inc, and two fully au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 33 publications
0
117
0
Order By: Relevance
“…The accuracy of homology modeling is highly dependent on the sequence similarity of the structural template(s) used, and for mAb variable domains, the framework modeling is generally successful (backbone RMSD < 1), as are the LC CDRs and HC CDRs 1 and 2. The CDR-H3 accuracy varies in homology modeling and this, 26,27 as well as sidechain conformational variation, can explain why the MD averaging improves experimental predictions. The conformational ensemble produced by LowModeMD likely smoothes out sensitivity in homology modeling, reducing error, especially when template quality is poor.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of homology modeling is highly dependent on the sequence similarity of the structural template(s) used, and for mAb variable domains, the framework modeling is generally successful (backbone RMSD < 1), as are the LC CDRs and HC CDRs 1 and 2. The CDR-H3 accuracy varies in homology modeling and this, 26,27 as well as sidechain conformational variation, can explain why the MD averaging improves experimental predictions. The conformational ensemble produced by LowModeMD likely smoothes out sensitivity in homology modeling, reducing error, especially when template quality is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this change is significantly lower than that of the other CDRs and is even smaller than the change in the FR and the constant domain (the baseline). It is not the shortest CDR, but it has the lowest number of contacts with the Ag (53), a low number of mutations during affinity maturation (55), and low structural diversity in different Abs (56). These observations may suggest that the conformational change that a CDR undergoes is related to its role in Ag binding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these mispredicted cases in the CDR-H3 region are also located on very long loops (length given in brackets): M97 (11), M100b (13), M100h (16), M100i (19) and M100* (20). This suggested that the failure of the model in these cases was most likely due to uncertainty in the CDR-H3 modeling, 32,33 which would affect the features extracted from these structures.…”
Section: Resultsmentioning
confidence: 99%
“…This becomes especially important for long CDR-H3 loops, where even state-of-the art models still lack reliability. 32,33 It is also worth noting that predictive power is directly influenced by dataset size; therefore, the current model can be further improved (especially to minimize the number of false positives), with increased dataset size (specifically, liable Met) in the future. Some studies have shown that residues that fall outside of the traditionally defined CDRs can also be important to antigen binding, 37 which suggests that molecular assessment studies may need to be further extended to these residues.…”
Section: Discussionmentioning
confidence: 99%